A Wicked View. Issue 4 (29th June 2017) - Barrett, Michael; Ervin, David E.; Frisvold, George B.; Jussaume, Raymond A.; Shaw, David R.; Ward, Sarah M.
Abstract : In a recent essay, Harker and coauthors stated that considering herbicide resistance as a wicked problem "without clear causes or solutions" ignores what weed scientists know about the biology and management of herbicide-resistant weeds. In this response, we argue that this misrepresents what is meant by "wicked" and that the wicked problem concept is valuable in understanding the multifaceted nature of herbicide resistance as a human-caused phenomenon.